Le féminin délinquant : le féminisme de Mary Wollstonecraft - Nathalie Zimpfer (XVII-XVIII, 2023)
This article offers a reading of Mary Wollstonecraft’s feminism from a philosophical perspective, resorting to concepts suggested by Jacques Rancière and Michel de Certeau. While various critics have focused their analyses on the agonistic dimension of Wollstonecraft’s feminism (Taylor, Halldenius), more attention is here devoted to the consequences of this positioning, in particular the disidentification preceding the process of political subjectivation (Rancière). That is why the emphasis is placed on the polemical discursive space created by Wollstonecraft through the publication of Vindication of the Rights of Men (1790) and its theorization in Vindication of the Rights of Woman (1792). It is this space which gives rise to Wollstonecraft’s specific brand of feminism : a “delinquent” (de Certeau) kind of feminism which makes it possible for women to transcend the limitations that constrained them at the time.